2020
DOI: 10.3390/nu12061661
|View full text |Cite
|
Sign up to set email alerts
|

The Role and the Effect of Magnesium in Mental Disorders: A Systematic Review

Abstract: Introduction: Magnesium is an essential cation involved in many functions within the central nervous system, including transmission and intracellular signal transduction. Several studies have shown its usefulness in neurological and psychiatric diseases. Furthermore, it seems that magnesium levels are lowered in the course of several mental disorders, especially depression. Objectives: In this study, we wish to evaluate the presence of a relationship between the levels of magnesium and the presence of psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 93 publications
2
79
0
2
Order By: Relevance
“…A number of enzymes and cellular reactions involved in stress responses are Mg-dependent [ 15 ]. Serum Mg levels have been proposed to be reduced in subjects with depression [ 138 ]. A recent study by Noah et al showed that nearly half (forty-four percent) of patients screened for stress had a latent Mg insufficiency [ 139 ].…”
Section: Mg and Psychiatric Disordersmentioning
confidence: 99%
“…A number of enzymes and cellular reactions involved in stress responses are Mg-dependent [ 15 ]. Serum Mg levels have been proposed to be reduced in subjects with depression [ 138 ]. A recent study by Noah et al showed that nearly half (forty-four percent) of patients screened for stress had a latent Mg insufficiency [ 139 ].…”
Section: Mg and Psychiatric Disordersmentioning
confidence: 99%
“…Some studies in murine models of disease revealed the positive role of magnesium in neuroinflammation reduction ( 79 , 80 ). The large majority of studies carried out so far in patients have been focused on depression, because of the well-known involvement of magnesium in several core mechanisms of depressive pathophysiology, including inflammation and oxidative stress ( 81 ). Among others, investigations proposed that magnesium could relieve depression by blocking the NMDA receptor, whose dysfunction is a major causative factor in depression pathology ( 82 ).…”
Section: Depression Bipolar Disorders Obsessive-compulsive Disordermentioning
confidence: 99%
“…The candidate markers regard different biological systems including genetics, immunity, brain changes and metabolism [ 15 , 16 , 17 ]. Among these, the metabolic hypothesis is particularly promising as it integrates genetic vulnerability with environmental aspects [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%